2021
DOI: 10.1002/acr.24435
|View full text |Cite
|
Sign up to set email alerts
|

Quality Improvement Intervention to Reduce Thirty‐Day Hospital Readmission Rates Among Patients With Systemic Lupus Erythematosus

Abstract: Objective Systemic lupus erythematosus (SLE) has one of the highest 30‐day hospital readmission rates among chronic diseases in the US. This quality improvement initiative developed and assessed the feasibility of a multidisciplinary postdischarge intervention to reduce 30‐day readmission rates among SLE patients. Methods A retrospective study was performed using electronic health records of patients with SLE admitted to a university hospital prior to (nonintervention group) and after initiation of the study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The different MD teams mostly employed an approach that pivoted on the periodical standard clinical evaluation of the patients (11/19, complemented in 3/19 studies by psychotherapy sessions), regardless of the healthcare professionals involved. In 4/19 cases, intervention focused on gathering information through in-person meetings or phone calls, without the direct involvement of a rheumatologist [ 12 , 15 , 21 , 23 ]. Except for the management of pregnancy-related and psychological issues in SLE, we found heterogeneous examples of MD approaches to SLE patients.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The different MD teams mostly employed an approach that pivoted on the periodical standard clinical evaluation of the patients (11/19, complemented in 3/19 studies by psychotherapy sessions), regardless of the healthcare professionals involved. In 4/19 cases, intervention focused on gathering information through in-person meetings or phone calls, without the direct involvement of a rheumatologist [ 12 , 15 , 21 , 23 ]. Except for the management of pregnancy-related and psychological issues in SLE, we found heterogeneous examples of MD approaches to SLE patients.…”
Section: Resultsmentioning
confidence: 99%
“…Review of authors’ judgements about each risk of bias using NIH risk of bias tool. Green box = “yes/low risk of bias”; yellow box = “not applicable/not reported”; red box = “no/potential risk of bias” [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ].…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…During the first 2 years of IQ‐LUPUS, participants achieved a reduction in hospital admissions, 30‐day readmissions, and missed appointment rates. In another recently published study, investigators identified patients with SLE who were admitted to the hospital for any reason and sent a templated message to the rheumatology clinic nurses at discharge ( 23 ). This message prompted the nurses to contact the patient to assist with care coordination and education.…”
Section: Discussionmentioning
confidence: 99%